Deregulated systemic IL-10/IL-12 balance in advanced and poor prognosis paediatric soft tissue sarcomas. (May 2013) - Bien, Ewa; Krawczyk, Malgorzata; Izycka-Swieszewska, Ewa; Trzonkowski, Piotr; Kazanowska, Bernarda; Adamkiewicz-Drozynska, Elzbieta; Balcerska, Anna
Abstract Context: The roles of interleukin 10 (IL-10) and IL-12 in regulation of cancer growth and Th1/Th2 immune responses towards cancer are unclear. Objective: To establish the prognostic significance of serum IL-10 and IL-12 in paediatric soft tissue sarcomas (STS). Materials and methods: ELISA determinations of cytokines were performed as pre-treatment in 59 children with STS and 30 healthy controls. Results: Elevated IL-10 and decreased IL-12 serum levels correlated with advanced disease, poor response to chemotherapy and poor outcome. IL-10 ≥ 9.5 pg/ml, IL-12 ≤ 65 pg/ml and lymph nodes involvement independently predicted poor overall survival (OS) in multivariate Cox analysis. Conclusion: Serum IL-10/IL-12 balance determination may facilitate to assess risk groups and prognosis in childhood STS.